Social status of a civil servant: measurement criteria and determinants (Journal of Economic Research & Business Administration, 2023)
This work explores the social protection aspects of the public service system. Based on the literature review approach, it analyzes the conceptual framework of the social status of civil servants. The main goal is to reveal the criteria for determining the social status of public servants and the main factors affecting this type of status.The results of this study show that a widely accepted set of measures for determining the social status of civil servants includes economic, legal, and professional aspects of the civil service system. The public assessment, respect, and trust for civil servants constitute the fundamental base for building a positive image and prestige of the public servants in a society.The findings of this research can be used in the public service reform devoted to the social protection of public servants in Kazakhstan.The study was funded by the Science Committee of the Ministry of Science and Higher Education of the Republic of Kazakhstan (BR18574203).